Doping technique in the interfacial transition zone between paste and lateritic aggregate for the production of structural concretes - Ana Paula Moreno Trigo; Jefferson Benedicto Libardi Liborio (Materials Research, 2013)
This paper discusses the use of doping technique in the interfacial transition zone (ITZ) between Portland cement paste and lateritic aggregates with the objective of promoting the implementation of structural concrete. Doping technique consists of establishing the initial impregnation of the aggregate with a high performance paste in order to improve its binding to the matrix. A Scanning Electron Microscope (SEM) equipped with an energy dispersive X-ray (EDX) analysis system is used to observe the results of the technique in the ITZ. The results are observed through an analysis of the cement hydration products formed in the ITZ. An ITZ with high concentration of large crystals of calcium hydroxide (CH) is observed in plain concrete, whereas in concrete prepared with doping technique the ITZ is rich in calcium silicate hydrate (CSH). This result confirms the possibility of using this material, which has no commercial value nowadays, as an alternative aggregate for elaborating structural concrete.